Risk Management Analysis of Building Construction Project in the Jakarta City - Ahmad Waris Maulana; Budi Santosa (Jurnal Fondasi, 2020)
Building construction project is one of the projects that has a high risk based on the workload and the height of the building structure. Implementation of this construction takes a long and complex. Therefore, it can cause uncertainty of conditions in the field raises various risks in the implementation of the project. Risk management should apply at the initial phase for project development, risk management will be very useful in developing an understanding of project uncertainty. It is very important to understand the risk management concept before understanding the risks in building construction industry. This study aims to obtain the dominant most influential risk factors in a building construction project by using Relative Important Index (RII) Method. The RII method is used to look at the greatest risk factors. Primary data of the research were obtained by filling the risk factor questionnaire by 32 respondents with the positions of Consultans, Chief Expert, Project Manager, and Site Manager. The results showed that The events included in the high risk category are as follows; lack of detailed drawings, a change in design, the designs and drawings do not comply with the bill of quantity, the amount of labor is changing, lack of availability of workers, lack of control and coordination in the field, additional scope of work, inaccuracy and mismatch of detailed specifications on the design, lack of worker expertise and lack of qualified staff, error estimating costs and implementation time.